Ko-Kreasi dalam Ritual Nyomya Ogoh-Ogoh, Sebuah Community Event di Banjar Tainsiat - Wirjawan, Ignacia Andrea; Lestari, Ni Komang Melya; Ardianto, Eka; Jayawardhana, Irman (Pusat Studi Pariwisata Universitas Gadjah Mada, 2025)
This study aims to explore the co-creation that occurs between actors in a community event using narrative analysis and interpretation of the Freytag Pyramid of the Nyomya Ogoh-ogoh ritual held in Banjar Tainsiat, Denpasar City, Bali. The data used in this study were collected through semi-structured interview as well as the collection of audio and visual media which was carried out through event documentation on various social media platforms. Researcher focuses on the story of the interaction between actors during their participation in the Nyomya Ogoh-ogoh ritual sequence which can provide insight for researchers to dig deeper into the pattern of co-creation that occurs in a community event. The Findings of this study states the presence of co-creation in a community event like the Nyomya Ogoh-ogoh rituals such as Co-Innovating, Co-Developing, Co-Modifying, Co-Involving, dan Co-Participating. Based on these findings, several suggestions are presented for the organizing community and/or the event/tourism industry to implement co-creation in organizing various activities as well as several recommendations for further research to explore around this topic.